2012
DOI: 10.1186/1744-859x-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities in asperger syndrome and high functioning autism: diagnostic challenges

Abstract: Several psychiatric conditions, both internalizing and externalizing, have been documented in comorbidity with Asperger Syndrome (AS) and High Functioning Autism (HFA). In this review we examine the interplay between psychiatric comorbidities and AS/HFA. In particular, we will focus our attention on three main issues. First, we examine which psychiatric disorders are more frequently associated with AS/HFA. Second, we review which diagnostic tools are currently available for clinicians to investigate and diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(152 citation statements)
references
References 84 publications
6
129
1
6
Order By: Relevance
“…However, some studies reported that girls with ASD appeared to be at greater risk than boys for internalizing psychopathology (Solomon et al 2012;Mazzone et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported that girls with ASD appeared to be at greater risk than boys for internalizing psychopathology (Solomon et al 2012;Mazzone et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In our sample, ADHD is the most frequent comorbid disorder (66%), specially presenting in childhood and puberty. In literature, the prevalence of ADHD among individuals with ASD is estimated to be 28.2% [3], particularly among those with HFA/AS it's 44% -65% [6]. These findings stress the clinical necessity to assess inattention and hyperactivity/impulsivity in ASD [10], and point out also the fact that often is difficult to establish early diagnosis of HFA/AS, because autistic symptoms could be masked by ADHD symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible to recognize obsessions/compulsions from ASD repetitive behaviours, [6], but standardized diagnostic tools are currently not yet available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations